The healthy, yet unhealthy choice: stereotypes about vegetarians and vegans in a meat-eating culture - Branković, Marija; Budžak, Anastasija (Primenjena psihologija, 2024)
Stereotypes about vegetarians and vegans influence behaviour toward these groups and the consumption of animal products. This affects the health and well-being of humans, other animals, and the environment. We studied these stereotypes in a meat-eating culture based on content analysis of open-ended responses in contrast to the more frequently used ad-hoc scales. We also compared the positivity and contents of stereotypes between men and women and between vegetarians/vegans and meat-eaters. We found that stereotypes about vegetarians are ambivalent, while stereotypes about vegans are more clearly negative, both to a greater extent among meat-eaters and among men. The open-ended responses were most frequently related to health, then to moral values, empathy, commitment, and unfavourable social traits. References to masculinity/femininity were not prominent in the spontaneous responses, and neither was the domain of competence. While meat-eaters mainly relate vegetarianism and veganism to health, vegetarians/vegans relate these choices to empathy and moral values. We discuss the implications of the findings for cross-cultural research and shaping public communications.